The influence of an extreme drought event in the fish community of a southern Europe temperate estuary - Martinho, F. (2007)
Between 2003 and 2006, a severe drought occurred throughout the Mondego River catchment's area, inducing lower freshwater flows into the estuary. As a consequence, both 2004 and 2005 were considered as extreme drought events. From June 2003 to June 2006, the fish assemblage of the Mondego Estuary was sampled monthly in five stations during the night, using a 2 m beam trawl. Fish abundance was standardized as the number of individuals per 1000 m2 per season and the assemblage was analyzed based on ecological guilds: estuarine residents, marine juveniles, marine adventitious, freshwater, catadromous and marine species that use the estuary as a nursery area. A total of 42 species belonging to 23 families were identified, with estuarine residents and nursery species dominating the fish community. Variations in the fish community were assessed using non-metric MDS, being defined as three distinct periods: summer and autumn 2003, 2004/2005 and winter and summer 2006. The main drought-induced effects detected were the depletion of freshwater species and an increase in marine adventitious in 2004/2005, due to an extended intrusion of seawater inside the estuary and a significant reduction in abundance during the driest period of estuarine resident species. Nevertheless, from the management point of view, it could be stated that although some variations occurred due to environmental stress, the main core of the Mondego Estuary fish community remained relatively unchanged.